E-Point Septal Separation: A Bedside Tool for Emergency Physician Assessment of Left Ventricular Ejection Fraction (Bangladesh Critical Care Journal, 2023)
Introduction: Rapid assessment of left ventricular ejection fraction (LVEF) may be critical among emergency department (ED) patients. This study examined the predictive relationship between bedside mitral-valve E-point septal separation (EPSS) measurements to the quantitative calculated LVEF.Objective: The aim of this study was to investigate the ability of a new index, namely the mitral valve E-Point Septal Separation (EPSS ) to predict the left ventricular (LV) systolic function.Methods: A prospective observational study was conducted on a sequential convenience sample of patients, receiving comprehensive Transthoracic Echocardiography (TTE). The current study recruited 100 patients who presented to the Cardiology Clinic of Lab Aid Cardiac Hospital. Echocardiographic examinations were performed to obtain 2D guided M-mode measurements of the EPSS in addition to calculation of conventional, quantitative LVEF. All the measurements were done in the Para-sternal long-axis view. A linear regression analysis was conducted to examine the relation of EPSS to the calculated LVEF from the comprehensive TTE.Results: Total 100 patients were enrolled in the study. It was found that there was a very significant negative correlation of EPSS with Calculated LVEF (r=--.766, p